Langerhans cell histiocytosis involving the temporal bone with destruction and subsequent reossification of the bony labyrinth boundaries - Döring, Katja; Ivanyi, Philipp; Lanfermann, Heinrich; Warnecke, Athanasia; Giesemann, Anja (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Purpose With an incidence between 1–9/100 000 per year, Langerhans cell histiocytosis (LCH) is a rather rare disease from the hemato-oncologic disease spectrum (Hayes et al. 2009). The tumorlike disease with proliferation of histiocytic cells may manifest as localized to one organ or disseminated with infiltration of a wide variety of organs. Approximately 25–30 % of these cases show involvement of the temporal bone (Ni et al. 2017).Case Description With vertigo persisting for three years, chronic mastoiditis, and acute progressive hearing loss bilaterally (r > l) for three weeks, a 41-year-old woman presented at an emergency department. The DVT showed extensive bony destruction of large parts of the temporal bone on both sides, involving the vestibular organ, the cochlea, and the internal auditory canal. To confirm the suspicion of a systemic inflammatory process, a PE was performed from the mastoid with bioptic confirmation of an LCH. Systemic therapy was initiated. Post-therapeutic imaging showed almost complete remission with reossification of the preexisting defect zones and the internal auditory canal and labyrinth structures again showed bony margins. Clinically, there was an improvement of the vegetative symptoms with remaining bilateral sensorineural hearing loss.Discussion LCH of the temporal bone is a rare and often misdiagnosed disease due to its nonspecific clinical presentation. Awareness of temporal bone LCH and its occurrence in adults is essential for accurate and consistent diagnosis.Key Points:
Keywords: head/neck; CT; hematologic; chemotherapy